VICTIM PROTECTION IN THE CRIMINAL LEGAL SYSTEM: A RIGHTS-BASED JUSTICE APPROACH - Mawarni Fatma (PT. Anagata Sembagi Education, 2026)
The Indonesian criminal law system has historically been more oriented towards punishing perpetrators of crimes, so that the position of victims in the judicial process is often marginalized and their rights are not adequately fulfilled. The colonial legacy paradigm that positions the state as the injured party renders victims merely witnesses or pieces of evidence, rather than legal subjects with a direct interest in their recovery. This article aims to critically examine how victim protection can be realized through a rights-based justice approach within the framework of Indonesian criminal law, particularly following the enactment of Law Number 1 of 2023 concerning the Criminal Code. This study uses a normative juridical method with a legislative and conceptual approach, supported by secondary data in the form of laws and regulations, court decisions, and recent academic literature. The results of the study indicate that although legal instruments such as the right to restitution, compensation, rehabilitation, and physical and psychological protection have been regulated, their implementation still faces structural, cultural, and procedural obstacles, so that victims have not fully received proper redress. A rights-based justice approach offers a reorientation of the criminal justice paradigm from one centered on the state and perpetrators to one that positions victims as legal subjects with rights to participation, information, protection, and redress. This article recommends institutional strengthening, regulatory harmonization, and internalization of human rights-based restorative justice principles as strategic steps to achieve just and sustainable victim protection.